The emergency to tackle tobacco smoking by Lebanese adolescents. (30th September 2020) - Akel, M; Salameh, P; Ehlinger, V; Godeau, E
Abstract: In Lebanon, tobacco use by adolescents remains a problem and is higher than among adults. This study sought to assess the experimentation of tobacco smoking practices among adolescents in Lebanon, and further to link health promotion at school-level (measured with the Hat Questionnaire) to the smoking behaviour at students-level (measured with the HBSC questionnaire). We relied on a cross-sectional observational study, conducted in 50 schools across Lebanon. The students' ages ranged from 11 to 18 years old (6th to 12th grade). They filled-in a confidential, anonymous self-questionnaire in class. In parallel, the school administration filled in the assessment questionnaire for health promotion. STATA Software was used for statistical analysis.7133 students were included (mean age 15.24±2.00 years). Overall, 24.5% had ever experimented cigarette smoking alone, boys more than girls (31.95% vs. 19.14%; p < 0.001), mainly from Beirut (33.62%; p < 0.001) and with poor health perception (29.12% vs. 19.87%; p < 0.001). Overall, 33.98% had ever used water-pipe alone, again more boys (40.34% vs. 29.88%; p < 0.001), from Beirut (39.55%, p < 0.001), and with poor health perception (39.48% vs. 28.93%; p < 0.001). Finally, 22.28% experimented both cigarettes and water-pipe. Around 70% of the involved schools offered health-related courses in their curricula. 72 % of them included interventions on the harm of smoking but not as an integral part of the curriculum. Less than half of them had developed plans to improve health promotion and review data to ensure the effectiveness of their programs. This alarming rate of use of tobacco products constitutes a major public health issue for Lebanese adolescents that needs urgent intervention. Further analysis will focus on the school-level questionnaires. Already our results will serve to foster the reinforcement of health promoting schools in Lebanon by the ministry of Education, in line with international recommendations.